Paduan Ornamen Budaya Nusantara dalam Estetika Fasade Arsitektur Landmark Karya Wolff Schoemaker - Ganesha Wibisana; Arthur S. Nalan; Supriatna Supriatna (PANTUN, 2022)
Wolff Schoemaker is an architect who reads local culture in architectural works. Placement of archipelago ornaments in the facade of the Landmark building forms an architectural blend of western aesthetics with rational understanding and eastern concepts with cultural symbols. The method used in this research is qualitative, which is described in an interpretive descriptive manner. The study uses the aesthetic theory of Edmund Burke Feldman with his formulation regarding four aspects, namely function, structure, style and meaning. This concept produces a model of formalism and symbolic analysis as part of the aesthetic meaning of architecture. Pepatraan ornaments on the shape of the building are equipped with the heads of Kala and Makara as the application of the decoration in the façade. It forms Landmark architecture with the concept of west and east. The placement of Kala is influenced by the concept of Total Work of Art in the Jugendstil style in Europe by placing figurative ornaments in accordance with formal aesthetic principles. The eastern concept is seen in the left and right sides of the building which has a shape similar to the temple architecture. It applies to the Kala ornament in the middle, so that the aesthetic appeal of the Landmark consists of the aspects of formal and symbolic form.Keywords: Ornament, Architecture, Kala, Wolff Schoemaker